HISTORIOGRAPHY OF THE RELIGIOUS POLICY OF THE SOVIET GOVERNMENT IN THE UZBEK SSR - Boburmirzo Zuhriddin o‘g‘li Najmiddinov (Modern American Journals, 2025)
This article discusses the work carried out during the Soviet era, the work done by national researchers after independence, and the historiography of scientific works carried out by foreign researchers, which illuminate the religious policy pursued by the Soviet government in the Uzbek SSR. In the Soviet period, the interpretation of these works was carried out mainly from the point of view of ideology, and one can see a one-sided assessment of the policy of that time. During the years of independence, the history of this period began to be covered objectively, and foreign scholars gave an objective assessment, free from ideology.
Keywords: Soviet power, Uzbek SSR, historiography, scientific works, monographs, articles, Soviet historiography, atheistic views, ideological approach, works during the period of independence, foreign scholars, objective approach.